ANALISIS REFERENSI DAN FRASA NOMINAL TERHADAP KARAKTER DILAN DALAM NOVEL DIA ADALAH DILANKU 1990 - Widyasana, Boris Candra (Universitas Sebelas Maret, 2023)
This study aims to describe the use of nominal phrases that show the characterisation of Dilan in the novel Dia adalah Dilanku 1990. This type of research is descriptive qualitative research with syntactic and semantic approaches. The data sources used are sentences containing reference words and noun phrases that present Dilan's characterisation in the novel Dia adalah Dilanku 1990 series by Pidi Baiq. The method of note-taking and reading were conducted in this research. The result of the research shows that there are general pointer demonstrative reference words and third person personal pronominal to characterise Dilan. The types of phrases used in this novel are attributive endocentric, coordinative endocentric, and exocentric nominal phrases.